Holiday and weight gain: Evidence from National Day holiday in China - Hengrong Luo; Xiaohua Yu (Georg-August-Universität Göttingen, Research Training Group (RTG) 1666 - GlobalFood, 2020)
We use the regression discontinuity model and CHNS (China Health and Nutrition Survey) data, to study the body weight gain effect of the National Day holiday in China. We find that Chinese adults tend to gain 1.561 kg during the National Day holiday. The weight gain effect shrinks to 0.967 kg or even 0.491 kg, when we extend the time window from one-week level to two-week level and the one-month level. It implies that holiday weight gain could lead to the long-term body weight accumulation. Besides, the middleage group is the most fragile group to the holiday weight gain. Young and middle aged males and old females suffer more to the weight gain compared to their counterpart.
Keywords: I12; I18; 330; Holiday weight Gain; National Day holiday; Regression discontinuity; obesity